YOUTUBER’S BACKGROUNDS THAT IMPACT ERROR IN TRANSLATION - I GUSTI NGURAH OCTOVA SEVENTILOFA (Universitas Mahasaraswati K. Mataram, 2023)
This research is an example of qualitative research where the focus is on explaining phenomena that occur in everyday social life. The purpose of this study is to provide a brief description of what background factors influence a Youtuber's ability to translate language, especially from Indonesian to English, so that errors occur. The objects of this research are several original Indonesian Youtubers who actively display content on the Youtube platform, where these Youtubers have posted videos or content in English. Based on the results of the research conducted, there are 3 background factors that affect errors in their translation ability, namely; educational background, economic background, and social background.